PERBEDAAN KABAR HEMOGLOBIN PADA PASIEN ANEMIA SEBELUM DAN SESUDAH VAKSIN COVID 19 - Edi Suriaman; Nugroho Tristyanto (Klinikal Sains : Jurnal Analis Kesehatan, 2023)
Anemia is a condition in which there is a decrease in hemoglobin, erythrocyte and hematocrit levels so that the number of circulating erythrocytes and hemoglobin levels cannot fulfill their main function. Anemia that does not get treatment will result in hypoxia and lead to organ dysfunction, especially breathing. It is this organ dysfunction that makes COVID-19 disease worse. Governments must be prepared to ensure access to and distribution of COVID 19 vaccines on a large and equitable scale if and when a safe and effective vaccine becomes available. Until this article was written in 2022, the total number of confirmed cases from around the world was 476 million cases with 6.1 million confirmed deaths due to COVID-19 infection to the latest variant. The research design is an analytic research with a cross-sectional data collection approach. The data sources used in this study were primary data obtained from before and after hemodialysis to determine the patient's hemoglobin level and secondary data obtained from medical records to determine the sample according to the inclusion and exclusion criteria. In this study, the samples to be taken were anemic patients who received the Covid-19 vaccine, a total of 30 patients. it can be seen that the respondents aged 18-65 years or a number of 24 respondents (80%). It is known that the results of the study found differences in hemoglobin levels before and after the covid - 19 vaccine from 30 patients on examination of the hemoglobin level values ​​before the covid - 19 vaccine obtained the highest hemoglobin level value of 13.3 g/dL and the lowest hemoglobin level value of 7.0 gd /L with an average obtained of 8.66 gd/L while in the description of the value of hemoglobin levels after the covid-19 vaccine the highest hemoglobin level value was 13.5 g/L and the lowest hemoglobin level value was 7.0 gd/L with the average obtained was 9.10 g/dL